2009
DOI: 10.1007/978-1-59745-483-4_35
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles for Local Drug Delivery Using Magnetic Implants

Abstract: This chapter is a brief description of the state of the art of the field of targeted drug delivery using magnetic implants. It describes the advantages and drawbacks of the use of internal magnets to concentrate magnetic nanoparticles near tumor locations, and the different approaches to this task performed in vitro and in vivo reviewed in literature are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…16 Accumulating research findings have shown that nanotechnology and nanoparticles are becoming a focus for application in clinical medicine because of their stable biomolecular absorption, high surface energy, and small size comparable with biomolecules. 27,28 Our present study shows that gambogic acid can inhibit Figure 1B), indicating that magnetic nanoparticles containing Fe 3 O 4 themselves had no cytotoxicity, which is consistent with current research. 29 Our study also provides evidence that the apoptosis ratio in LOVO cells treated with an optimal combination of gambogic acid and Fe 3 O 4 magnetic nanoparticles increased dramatically compared with cells treated with gambogic acid alone (P , 0.05, Figure 2), which confirms that magnetic nanoparticles containing Fe 3 O 4 and gambogic acid have a synergistic effect on LOVO cells.…”
Section: Discussionsupporting
confidence: 92%
“…16 Accumulating research findings have shown that nanotechnology and nanoparticles are becoming a focus for application in clinical medicine because of their stable biomolecular absorption, high surface energy, and small size comparable with biomolecules. 27,28 Our present study shows that gambogic acid can inhibit Figure 1B), indicating that magnetic nanoparticles containing Fe 3 O 4 themselves had no cytotoxicity, which is consistent with current research. 29 Our study also provides evidence that the apoptosis ratio in LOVO cells treated with an optimal combination of gambogic acid and Fe 3 O 4 magnetic nanoparticles increased dramatically compared with cells treated with gambogic acid alone (P , 0.05, Figure 2), which confirms that magnetic nanoparticles containing Fe 3 O 4 and gambogic acid have a synergistic effect on LOVO cells.…”
Section: Discussionsupporting
confidence: 92%
“…12 Nanotechnologies and nanoparticles are becoming a focus for human medical application for their unique properties. 13 The diagnostic and therapeutic applications of magnetic iron oxide nanoparticles such as drug delivery, magnetic resonance imaging, hyperthermia techniques, cell separation, and tissue repair have expanded enormously in recent decades. 14 The application of drug-coated polymer nanospheres and nanoparticles to inhibit the related drug resistance has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature also has an effect in the stability of the magnetic nanoparticle due to energy transfer from the solvent molecules (Brownian motion) to the nanometric particles. Hence, magnetic nanoparticle can be coated with a biocompatible polymer to enhance its stability [30,31,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Magnetic Nanoparticlementioning
confidence: 99%